Never say die : would they have what it takes to make it out alive - McCollum, Sean (New York : Scholastic Inc., 2012)
Trapped in a lonely Utah canyon, Aron Ralston was forced to confront the unthinkable in order to make it out alive. Left for dead on an icy mountain in Peru, Joe Simpson faced a choice: drag himself to camp on a shattered knee or die alone 4000 miles from home.
Atrapado en un solitario cañón de Utah, Aron Ralston se vio obligado a enfrentarse a lo impensable para salir con vida. Abandonado por muerto en una montaña helada en Perú, Joe Simpson se enfrentó a una elección: arrastrarse hasta el campamento en una rodilla recién descubierta o morir solo a 4000 kilómetros de su casa.
CONTENTS ESCAPE FROM BLUE JOHN CANYON: ARON RALSTON BEYOND THE BRINK: JOE SIMPSON A CONVERSATION WITH THE AUTOR WHAT TO READ NEXT
Keywords: NORTH AMERICAN LITERATURE -- NOVEL